PENGARUH SISTEM REWARD DAN STRESS KERJA PADA KINERJA KARYAWAN PADA PT. PLN (PERSERO) WILAYAH SULUTTENGGO - Keman, Lia Madelien; Tumbuan, Willem Alfa (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Abstract : Employee performance is an important thing in a company or organization. It plays a vital role because of the company or organization depends on their performance. There are many factors that impact the performance such as reward system and job stress. The objective of this research is to know the impact of reward system and job stress on employee performance. This research used a quantitative method, and the method to analyse the data applied by using Multiple Regression Analysis. This research use causal type of research where it will investigate the impact of reward system and job stress on employee performance. The population observed is the employees in PT PLN Wilayah Suluttenggo Office Manado with sample size as many as 100 respondents. This study reveals that Reward System has positive significant influence on employee performance and Job Stress has negative significant influence on employee performance. Keywords : Employee Performance, Reward System, Job Stress